Maintenance Optimization for Two-Component Series Systems With Degradation Dependence - Ma, Wei-Ning; Li, Hua; Yang, Zhi-Yuan; Hu, Qi-Wei (IEEE access, 2021)
This paper proposes a model of maintenance optimization for a system consisting of two dependent components in long-term operation, where both components are subject to dependent degradation. Gamma process is used to model the degradation, and Frank Copula is applied to describe the degradation dependence between the two components. We then consider degradation dependence to optimize maintenance strategy for the system to maximize its availability. The improved Artificial Bee Colony (ABC) algorithm is used to jointly determine inspection interval, opportunistic and preventive maintenance thresholds of the system. Finally, an example is provided to validate the proposed model.